Storage space reduction in picture archiving and communication system using generative adversarial network. (12th May 2023) - Varghese, Bejoy; Krishnakumar, S.
This paper presents a new architecture of picture archiving and communication system (PACS) based on generative adversarial network (GAN) and fractal image compression (FIC). The GAN architecture is modified to be a conditional GAN by conditioning the generator with the uncompressed image. Both the generator and discriminator networks utilise the convolutional neural network (CNN) which enables the system to capture the similarity measures without using any handcrafted functions. Performance of the proposed design is evaluated by comparing it with the commonly used compression techniques in PACS and recently reported best performing machine learning compression techniques. The simulation of PACS shows that the storage space consumption of the proposed design is only 30% in comparison with other algorithms. It is also observed that the GAN-based FIC can drastically reduce the compression time compared to the conventional fractal and non fractal compression methods.